Β-catenin as a regulator and therapeutic target for asthmatic airway remodeling. (September 2014) - Kumawat, Kuldeep; Koopmans, Tim; Gosens, Reinoud
<x xml:space="preserve">Abstract</x> Introduction: Pathological alteration in the airway structure, termed as airway remodeling, is a hallmark feature of individuals with asthma and has been described to negatively impact lung function in asthmatics. Recent studies have raised considerable interest in the regulatory role of β-catenin in remodeling asthmatic airways. The WNT/β-catenin signaling pathway is the key to normal lung development and tightly coordinates the maintenance of tissue homeostasis under steady-state conditions. Several studies indicate the crucial role of β-catenin signaling in airway remodeling in asthma and suggest that this pathway may be activated by both the growth factors and mechanical stimuli such as bronchoconstriction. Areas covered: In this review, we discuss recent literature regarding the mechanisms of β-catenin signaling activation and its mechanistic role in asthmatic airway remodeling. Further, we discuss the possibilities of therapeutic targeting of β-catenin. Expert opinion: The aberrant activation of β-catenin signaling by both WNT-dependent and -independent mechanisms in asthmatic airways plays a key role in remodeling the airways, including cell proliferation, differentiation, tissue repair and extracellular matrix production. These findings are interesting from both a mechanistic and therapeutic perspective, as several drug classes have now been described that target β-catenin signaling directly.